Improvement of Livestock Product Delivery Services Using Design Thinking - Mochamad Khilmi (Publikasi Indonesia, 2024)
PT. Charoen Pokphand Indonesia, the largest livestock company in Indonesia, was established in 1972 as PT Charoen Pokphand Indonesia Animal Feedmil Co. Limited. Today, the company is expanding with a focus on livestock activities such as broiler breeding, poultry slaughterhouses, and packing, processing of meat and poultry products, cultivation of broiler chickens, and a large trade in live animals and chicken meat. This study aims to identify the obstacles that occur in the process of shipping chickens, both experienced by farmers and by chicken expedition companies. In addition, this research also aims to improve livestock product delivery services by applying the Design Thinking approach. In the context of the livestock industry, the delivery of products such as live DOC chickens requires special handling, especially related to temperature and humidity, considering the vulnerability of DOC chickens to environmental changes. With a focus on partner logistics companies PT. Charoen Pokphand Indonesia, namely CV. Joint Work. The researcher included the Design Thinking method. The results of this research are expected to make a significant contribution to improving the quality of livestock product delivery services, improving operational efficiency, and providing a better experience for stakeholders.